Ethnoecology: The Community Adaptation Patterns of Forest Management in Grobogan Central Java - Fatmawati, Noor; Sanusi (Foresty Faculty of Hasanuddin University, 2024)
The aims of this research are to describe community adaptation patterns and determine community perceptions regarding forest environmental management. This qualitative research was studied using an ethnoecological approach with the research focus being the people of the Perhutani area of ​​Grobogan Regency. This research carried out the data collection through interviews, observation and documentation, with the main informant being Pesanggem as a forest land manager. This research produced the first findings in the form of community adaptation patterns in managing the environment covering three aspects, namely ecological adaptation, economic adaptation and social adaptation in the Pesanggem community in Gedangan Village, Wirosari District under the auspices of BKPH Sambirejo. 1) Ecological adaptation in Pesanggem showed the availability of well water which previously only relied on rainwater, then adjustments to various types of plants, as well as an understanding of prohibitions and sanctions for illegal activities in forest areas; 2) economic adaptation showed an increase in income for Pesanggem from forest land management; 3) social adaptation showed the existence of cooperation between members and other farmer groups within the LMDH forum. The second finding is that the public's perception in interpreting environmental management is that there are 5 values, namely the values ​​of wisdom, independence, religion, creativity and healthy living. Based on the research results, the author recommends that forest area communities be involved in managing and guarding forests for generational sustainability, and Perum Perhutani should invite partners from surrounding school institutions as a means of educating generations in joint forest management.